Chemical Constituents of Hedyotis dichotoma and their Biological Activity - Othman, Salwati; Hamzah, Ahmad Sazali; Aimi, Norio; Lajis, Md Nordin (Universiti Putra Malaysia Press, 1996)
Two compounds, isovitexin and ursolic acid, were isolated from the aerial parts of Hedyotis dichotoma. Anti-microbial assays indicated that isovitexin was active against fungus and candida. The structures of both compounds were assigned using modern spectroscopic techniques.